Stabilization Strategies for Fast Walking in Challenging Environments With Incomplete Spinal Cord Injury - Cornwell, Tara; Woodward, Jane; Ochs, Wendy; Gordon, Keith E. (Frontiers in Rehabilitation Sciences, 2021)
Gait rehabilitation following incomplete spinal cord injury (iSCI) often aims to enhance speed and stability. Concurrently increasing both may be difficult, though, because certain stabilization strategies will be compromised at faster speeds. To evaluate the interaction between speed and lateral stability, we examined individuals with (n=12) and without (n=12) iSCI as they performed straight walking and lateral maneuvers at Preferred and Fast treadmill speeds. To better detect the effects of speed on stability, we challenged lateral stability with a movement amplification force field. The Amplification field, created by a cable-driven robot, applied lateral forces to the pelvis that were proportional to the real-time lateral center of mass (COM) velocity. While we expected individuals to maintain stability during straight walking at the Fast speed in normal conditions, we hypothesized that both groups would be less stable in the Amplification field at the Fast speed compared to the Preferred. However, we found no effects of speed or the interaction between speed and field on straight-walking stability (Lyapunov exponent or lateral margin of stability (MOS)). Across all trials at the Fast speed compared to the Preferred, there was greater step width variability (p=0.031) and a stronger correlation between lateral COM state at midstance and the subsequent lateral foot placement. These observations suggest that increased stepping variability at faster speeds may be beneficial for COM control. We hypothesized that during lateral maneuvers in the Amplification field, MOS on the Initiation and Termination steps would be smaller at the Fast speed than at the Preferred. We found no effect of speed on the Initiation step MOS within either field (p>0.350) or group (p>0.200). The Termination step MOS decreased at the Fast speed within the group without iSCI (p<0.001), indicating a trade-off between lateral stability and forward walking speed. Unexpectedly, participants took more steps and time to complete maneuvers at the Fast treadmill speed in the Amplification field. This strategy prioritizing stability over speed was especially evident in the group with iSCI. Overall, individuals with iSCI were able to maintain lateral stability when walking fast in balance-challenging conditions but may have employed more cautious maneuver strategies.